Effect of a vegetation fire event ban on hospital visits for respiratory diseases in Upper Northern Thailand. (4th February 2022) - Uttajug, Athicha; Ueda, Kayo; Seposo, Xerxes Tesoro; Honda, Akiko; Takano, Hirohisa
Abstract: Background: Upper Northern Thailand (UNT) has been episodically affected by air pollution from vegetation burning, which causes adverse respiratory health effects. However, no study has evaluated the effect of regulatory actions to prohibit vegetation burning on respiratory morbidity. We examined the effect of a burning ban enforced in May 2016 on hospital visits for respiratory diseases in UNT. Methods: This study used data from eight provinces in UNT. Analyses were conducted for January to April of 2014–2016 (before ban enforcement) and January to April of 2017–2018 (after ban enforcement). Particulate matter of 10 microns in diameter or smaller (PM10 ) concentrations, numbers of satellite fire hotspots and age-standardized rates of hospital visits for respiratory diseases before and after ban enforcement were compared. The effect of the ban on hospital visits for respiratory diseases was evaluated using an interrupted time-series analysis controlled for season-specific temporal trends, day of week, public holiday, temperature, relative humidity, number of hospitals and offset population, with gastrointestinal diseases as a negative control. A meta-analysis was performed to pool province-specific effect estimates. Results: The daily average PM10 concentration and the number of fire hotspots decreased after ban enforcement in all provinces in UNT, with percent changes ranging from 5.3 to 34.3% and 14.3 to 81.5%, respectively. The adjusted pooled effect estimates of hospital visits for respiratory diseases decreased by 9.1% (95% CI: 5.1, 12.9), whereas a null association was observed for gastrointestinal diseases. Conclusion: The burning ban had a positive impact on both air pollution levels and rates of hospital visits for respiratory diseases in UNT.